2007
DOI: 10.1002/humu.20473
|View full text |Cite
|
Sign up to set email alerts
|

Partial duplication atAZFcon the Y chromosome is a risk factor for impaired spermatogenesis in Han Chinese in Taiwan

Abstract: The Azoospermia Factor c (AZFc) region on the Y chromosome long arm is one of the least stable regions in the human genome. It consists almost entirely of very long repeats and is prone to rearrangement. Numerous structures at AZFc have been identified, and some of them have been reported to be associated with male infertility. We screened 580 Han Chinese in Taiwan for AZFc deletion and duplication using three PCR assays, and characterized the DAZ genes in selected subjects with additional Southern analyses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 44 publications
(60 reference statements)
13
90
1
4
Order By: Relevance
“…In conclusion, discrepant results were detected regarding gene copy loss when multiple SFVs were compared in 27% (4/15) of DAZ3/DAZ4 deletions and 13% (1/8) in DAZ1/DAZ2 deletions. These Wgures are concordant with other studies in which these eVects have previously been reported as a consequence of gene conversion Lin et al 2007;Navarro-Costa et al 2007;StouVs et al 2008). …”
Section: Daz and Cdy1 Gene Copy Dewnitionsupporting
confidence: 93%
See 2 more Smart Citations
“…In conclusion, discrepant results were detected regarding gene copy loss when multiple SFVs were compared in 27% (4/15) of DAZ3/DAZ4 deletions and 13% (1/8) in DAZ1/DAZ2 deletions. These Wgures are concordant with other studies in which these eVects have previously been reported as a consequence of gene conversion Lin et al 2007;Navarro-Costa et al 2007;StouVs et al 2008). …”
Section: Daz and Cdy1 Gene Copy Dewnitionsupporting
confidence: 93%
“…Ours is the Wrst study in a Caucasian population and the discordance with the only study reporting such an association, based on a Han-Chinese population (Lin et al 2007), may reXect genuine ethnic diVerences or related to diVerent sample sizes. Table 5 Comparison of gr/gr deletion frequencies between the following three diVerent study populations: Giachini et al (2005); replication of the previous study on an independent sample set; combination of the two study populations a Twenty-nine subjects with a history of monolateral cryptorchidism originating from the Giachini et al 2005 …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…9,10 In addition to the classical AZFc deletion, several recurrent partial deletions (named gr/gr, b2/b3 and b1/b3) and duplications (b2/b4 duplication) have been reported. 11,12 Even though all partial rearrangements produce either a decrease or an increase in AZFc gene dosage, only the 'gr/gr deletion' resulted to be clinically relevant. The clinical significance of this recurrent deletion has been object of a long-lasting debate.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only two groups have addressed this topic in the Taiwanese and Italian populations, reaching contradictory conclusions. 12,20 In addition, by using a consecutive cohort study model, Noordam et al 21 suggested that both lower and higher DAZ gene dosage could be deleterious for spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%